Pengaruh Ukuran Perusahaan, Profitabilitas Dan Pertumbuhan Penjualan Terhadap Tax Avoidance Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019-2021 - Laura Theresia; Dini Hariyanti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to examine wether the effect of Company Size, Profitability, and Sales Growth on Tax Avoidance in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX). The method used in this research is associative with a quantitative approach. The population used in this study are 13 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The samples selected based on the purposive sampling method were 7 companies. The data used is secondary data. The collected data were analyzed using the Eviews 9 program. Based on the processed data that has been collected and the results of tests that have been carried out on research, the following conclusions can be drawn: (1) Company size affects tax avoidance (2) Profitability affects tax avoidance (3) Sales growth affects tax avoidance.